2018
DOI: 10.1159/000487066
|View full text |Cite|
|
Sign up to set email alerts
|

Is Prevalence of Hypertension Increasing in First-Ever Stroke Patients?: A Hospital-Based Cross-Sectional Study

Abstract: Background: Stroke is a devastating and disabling cerebrovascular disease with some amount of residual deficit leading to economic loss. Recent Indian studies have shown a stroke prevalence rate of 471.58/100,000 populations. Hypertension has been known to be the main risk factor for causing stroke. Purpose: To investigate the prevalence of hypertension in first-ever stroke patients and its comparison with the previous stroke registry. Methods: The study was a hospital-based cross-sectional study. Consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
1
14
1
Order By: Relevance
“…Our study reveals that older PLHIV who had ever been diagnosed with stroke were three times more likely to have hypertension as compared to their counterparts who have never been diagnosed with stroke. The present study is consistent with findings from a hospital-based survey that showed that hypertension increased among persons who have ever been diagnosed with stroke for the first time [ 30 ]. It is unclear how and why the risk of hypertension is high among persons who have ever been diagnosed with stroke.…”
Section: Discussionsupporting
confidence: 92%
“…Our study reveals that older PLHIV who had ever been diagnosed with stroke were three times more likely to have hypertension as compared to their counterparts who have never been diagnosed with stroke. The present study is consistent with findings from a hospital-based survey that showed that hypertension increased among persons who have ever been diagnosed with stroke for the first time [ 30 ]. It is unclear how and why the risk of hypertension is high among persons who have ever been diagnosed with stroke.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, it has been shown that lowering blood pressure can decrease the risk of stroke by 30 to 40% [ 32 ]. Though hypertension is the main reported risk factor of stroke among the included studies, the proportion of hypertension among stroke patients found in the current study is lower than previous studies conducted in India, Bosnia-Herzegovina, Zambia, Nigeria, Malawi, and Bangladesh [ 33 38 ]. The possible explanation for this variation might be due to the lack of diagnostic modalities and proficiency [ 39 ].…”
Section: Discussioncontrasting
confidence: 88%
“…This is consistent with the other study in this subcontinent. In Pakistan, Assad et al (2018), Manosalva and Jeerakathil (2016), Taj et al (2010) and in India, Pathak et al (2018) found hypertension 62.7%, 71%, 78% and 65% respectively. This finding is also consistent with a study in the Middle East, Korea as Kim et al (2003), Rukn et al (2019) found hypertension as 66% and 61.1% respectively.…”
Section: Discussionmentioning
confidence: 88%